Prior brief meditation reduces distractor inhibition during cognitive interference - Fujino, Masahiro; Ooishi, Yuuki; Ueda, Yoshiyuki; Kitagawa, Norimichi; Nomura, Michio (Frontiers in Psychology, 2024)
Background: Mindfulness meditation, comprising focused attention and open monitoring meditations, has been shown to enhance performance on cognitive interference tasks. While this enhancement has been considered not to result from distractor inhibition, no empirical evidence has been provided through behavioral data. In this study, we investigated whether 30-minute interventions of focused attention and open monitoring meditations could reduce distractor inhibition in 72 meditation-naïve participants divided into focused attention meditation, open monitoring meditation, and control groups. Methods: We employed a task set that combined a cognitive interference task with subsequent preference judgment and surprise recognition tasks, utilizing the mere exposure effect paradigm, along with state and trait questionnaires. The mere exposure effect shows that repeated exposure to face images increases one's preference for them. However, this effect is reduced if participants consciously or unconsciously try to inhibit the face images during stimulus processing. In the cognitive interference task, they judged the direction of the letter superimposed on a distractor face image. In the subsequent preference judgment task, they were asked to rate the preference of face images, half of which were presented in the interference task and the remaining half were not presented. We hypothesized that inhibiting face images presented as distractors would lead to a decrease in preference for them. Results & Discussions: We found that the mere exposure effect was observed in focused attention meditation and open monitoring meditation groups but not in the control group, indicating that compared to the control, focused attention and open monitoring meditations reduce inhibition processes for distractors during cognitive interference tasks. Furthermore, we found a positive correlation between the intensity of the mere exposure effect and state relaxation before the cognitive interference task as well as a negative correlation between the intensity of the mere exposure effect and state anxiety in the focused attention meditation group, but not in the open monitoring meditation group. This suggests that the processes of reducing inhibition in focused attention and open monitoring meditations differ. Our findings contribute to understanding the attentional mechanisms underlying mindfulness meditation during cognitive interference.